Study of Solid Waste Collection in Karbala City - منى فائق علي (Journal of Engineering and Sustainable Development, 2009)
This research is a study of the solid wastes in Karbala city. This study includes the identification of solid waste characteristics (generation rates, physical components, moisture content, density). The examinations have been done on the waste for eight months with one examination in a month as a rate, for the period from December 2007. until July 2008. , to take into account the changes of the seasons. The results show that the rate of generation was 0.44 kg/ person/ day, the density of waste was 469 kg/m, and moisture content was 48%. A study of the principal components of the (leachate) which migrates from the solid waste at the dumping site was done, and samples were taken from the leachate at the dumping site for five-month from December 2007. until March 2008. Eight tests have been done (Biochemical oxygen demand, chemical oxygen demand, Alkalinity, calcium ions, Sodium ions, Total suspended solids, Total dissolved solids, and Iron ion. In addition to that , a management system has been achieved to manage the solid waste of the city in addition to the recommendations which guarantee to reduce the risks of this problem